Input–output balance of cadmium in typical agriculture soils with historical sewage irrigation in China. (15th December 2020) - Yan, Xiulan; Zhao, Wenchu; Yang, Xiao; Liu, Chuchen; Zhou, Yaoyu
Abstract: The gradual increase of cadmium (Cd) in soils has caused environmental and health risk, and it's important to study the accumulation trend to evoke the awareness of farmland safety management. This research during the period of March in 2017–2018 evaluated the input (irrigation, atmospheric deposition, fertilizer and pesticide application) and the output (runoff and seepage, grain and straw uptake) of Cd in contaminated farmland irrigated with sewage water in Hebei Province. The experimental results indicated sewage irrigation (51.03%), and atmospheric deposition (46.35%) were the main input pathways; Grain uptake (42.72%) and straw removal (50.71%) played a major role in output fluxes. The input-output balance (net transport fluxes) of Cd in the farmland were estimated to be +3621.68 ~ +8899.78 mg·(ha·yr) −1 under different conditions (sewage irrigation with straw returning/straw removal, clean water irrigation with straw returning/straw removal), representing there was a Cd inputting in the farmland during the study. Even in the case of the lowest net transport fluxes, the annual increase of Cd concentration in soils reached to 0.0014 mg/kg. Therefore, it's necessary to take action that cutting off those pathway inputs into farmland ecosystems, such as monitoring the water quality of irrigation water sources, applying fertilizer and pesticide properly. Furthermore, attentions need to be paid to the Cd input into the farmland and environmental risks that may arise while returning straw to the field for improving soil fertility and crop production. Graphical abstract: This study shows that it's necessary to abate pollution that cutting off those pathway inputs into farmland ecosystems, efforts should be devoted to the control of input pathways for reducing input fluxes. Image 1 Highlights: Sewage irrigation and atmospheric deposition were the primary pathway for inputting Cd in study area. Grain harvest and straw removal afford main contributions for outputting Cd in study area. For minimum inputting fluxes and maximum outputting fluxes, the farmland demonstrated a net inputting system of Cd.